Exercise in patients with non-small cell lung cancer - Wiskemann, Lea Josefine; Wiskemann, Joachim; Abel, Ulrich; Ulrich, Cornelia; Hummler, Simone; Thomas, Michael (Medicine and science in sports and exercise, 2014)
Purpose: This study aimed to evaluate the safety, feasibility, and effects of an 8-wk combined resistance and endurance exercise program in patients with advanced non-small cell lung cancer (NSCLC) during in- and outpatient care. Methods: In this intervention study, 40 patients with predominantly advanced NSCLC receiving simultaneous or sequential radiochemotherapy or chemotherapy alone were enrolled. For a period of 8 wk, patients were instructed to exercise at least five times per week during the inpatient setting and at least three times per week in the outpatient setting. Physical performance status (endurance capacity: 6-min walk test; strength capacity: handheld dynamometry), quality-of-life (Functional Assessment of Cancer Therapy-Lung), fatigue (Multidimensional Fatigue Inventory), and depression (Patient Health Questionnaire) were assessed at baseline (T0), after the exercise intervention (T1), and at a follow-up time point 8 wk later (T2). The primary end point was adequate adherence (feasibility) defined as completing at least two training sessions per week during a minimum of 6 wk. Results: Of 40 patients, 31 (77.5%) completed the postexercise assessment (T1) and 22 (55%) completed follow-up (T2). The stages were IIA (5%), IIIA (8%), IIIB (20%), and IV (67%), and the median age was 63 yr (range = 22-75 yr). Overall, adherence was 82% for those patients who completed T1, and 55% of the 40 participating patients fulfilled the adequate adherence criterion. Those who completed the intervention showed a significant improvement in the 6-min walk distance and in knee, elbow, and hip muscle strength after the intervention (T1). Quality of life, fatigue, and depression scores remained stable or declined slightly. Significant improvements in knee-muscle strength were also observed at T2. Conclusions: Exercise training is feasible in advanced and metastatic NSCLC patients during anticancer treatment. In this pilot study, endurance and strength capacity improved over time, indicating the rehabilitative importance of the applied intervention. To investigate the potential impact of exercise training in this patient group, a larger randomized trial is warranted.